New quantum Hermite–Hadamard-type inequalities for p-convex functions involving recently defined quantum integrals - Gulshan, Ghazala; Budak, Hüseyin; Hussain, Rashida; Ali, Muhammad Aamir (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5 We develop new Hermite–Hadamard-type integral inequalities for p-convex functions in the context of q-calculus by using the concept of recently defined T_q-integrals. Then thе obtained Hermite–Hadamard inequality for p-convex functions is used to get new Hermite–Hadamard inequality for coordinated p-convex functions. Furthermore, we present some examples to demonstrate the validity of our main results. We hope that the ideas and techniques of this study may stimulate further research in this field.